GAMBARAN PERILAKU MASYARAKAT DALAM PENANGGULANGAN DEMAM BERDARAH DENGUE DI NAGORI RAMBUNG MERAH KABUPATEN SIMALUNGUN TAHUN 2014 - dearman andri; Alam Bakti Keloko; eddy syahrial (Kebijakan, Promosi Kesehatan dan Biostatiskik, 2015)
AbstractDengue Hemorrhagic Fever (DHF) is a contagious disease that can infect humans ,anyone , anytime and anywhere . Dengue disease transmitted through the bite of aedesagepty. The occurrence of dengue cases in various places can not be separated from people'sbehavior . Therefore, the behavior of the community in the prevention of DengueHemorrhagic Fever (DHF) become an important and urgent issue to be investigated .This study is a descriptive survey research and aims to identify and analyze thepicture of the behavior of the community in the prevention of Dengue Hemorrhagic Fever inNagori Red Rambung Simalungun 2014. The results showed that the majority of surveyrespondents were in high school and most work as an entrepreneur. The knowledge of therespondent to prevent of Dengue Hemorrhagic Fever (DHF) were good. The attitude of therespondents to prevent DBD were quite well. The action of the respondents in quite well.Infrastructures to prevent Dengue Hemorrhagic Fever (DHF) were less category. The role ofhealth workers to prevent Dengue Hemorrhagic Fever (DHF) were quite good. The role ofcommunity leaders to prevent Dengue Hemorrhagic Fever (DHF) were less. The suggestionsin this research were need to be improved knowledge, attitudes and actions ofthe communityto prevent Dengue Hemorrhagic Fever (DHF) by more communication, information andeducation to the community on regular, improve the quality and quantity of infrastructure,the role ofhealth workers, and the community leaders in the future.